Efektifitas Program Employee Relations Terhadap Motivasi Kerja Karyawan PT Adira Dinamika Multifinance - Intan Leliana; Devy Putri Kussanti (Universitas Bina Sarana Informatika, 2018)
Abstract - The company which is a place for employees to grow and develop in the world of work can also be a comfortable second home if the working atmosphere is good and positive. Making employees not only as workers but also as work partners is one of the company's efforts in providing comfort and recognition the existence of employees. This can also be done by holding several internal activities for employees in order to reduce the level of saturation to increase employee motivation to work. Is PT Adira Dynamics Multifinance, one of the largest financing companies in Indonesia which in addition to upholding the principle of consumer comfort but also prioritizes the comfort and principle of family in a work atmosphere that will improve the performance and work of employees. One of the things that is done is by holding events / activities for employees through the employee relations event, which is a holiday event and having fun together for the entire company. In addition to that, the event was also held as a place to increase the closeness between employees and superiors and attenuate the gap between them. The event is designed with activities that are interesting, relaxed and filled with an atmosphere of humor.